Role of Tie2, CD14, Angiopoietin as Angiogenetic Markers in Hepatocellular Carcinoma Complicating Hepatitis C Virus Infection - El-Zahraa, M. Meghezel; Heba, A. Ahmed; Ashraf, A Askar; Emad, Eldin Nabil; Ashraf, Elyamany (Journal of Hematology and Oncology Research, 2019)
Background Identifying biomarkers for early detection of hepatocellular carcinoma (HCC) remains quite challenging. In this study we aimed to estimate the number of TIE2-expressing monocytes (TEMs) cells, which display pro-tumoral activities and are defined as CD14+, TIE2+, and angiopoietin-2; and its potential use as a possible diagnostic marker in HCC patients complicating HCV induced cirrhosis. Methods Current study was conducted on 112 patients. They were divided into two groups: Group I (78 patients) with HCC complicating HCV induced cirrhosis; and group II chronic hepatitis C patients (34 patients). Both groups were compared to (age and sex-matched) healthy persons as group III (38 persons). Result The number of the circulating TEMs: CD14+ and TIE2+ monocytes were significantly higher in the peripheral blood of HCC patients than HCV LC patients and healthy controls, sensitivity and specificity for HCC diagnosis were respectively: CD14 (89.7%, 83.3%), TIE 2 (76.9%, 83.3%), and Ang-2 (76.9%, 66.7%). Moreover, analysis of the P-value and the odd’s ratio showed that CD14 has the highest predictive value for HCC. Conclusion Our results suggest that TEMs and Ang-2can be used as diagnostic markers for HCC, especially among the high-risk group of patients.
Keywords: TEM; Angiopoietin 2; HCV; Hepatocellular Carcinoma.